(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Memories and Records: The Vaccine Archive explores both individual and collective memories of vaccination across geographic borders. This paper outlines the development of The Vaccine Archive and analyzes the visual culture of vaccines manifested in the archive collections. In examining the vaccine archives, the author argues that the visual culture of vaccination reinforces stereotypes and fear associated with vaccines, forming and disseminating the collective memory of vaccines.